Slat Noise Suppression Using Upstream Mass Injection - 黄华 李伟鹏 王福新 (Shanghai jiao tong da xue xue bao, 2013)
A new approach,mass injection near the slat cusp,is proposed for the suppression of slat noise.The mechanism and efciency of the slat noise suppression using upstream mass injection are numerically studied with hybrid Reynolds-averaged Navier-Stokes simulation/Large eddy simulation（RANS/LES）of a three-component high-lift model.Ffowcs-Williams and Hawking（FW-H）integration is employed to obtain far-field acoustic characteristics.Results show that with injection,aerodynamic capability of the high-lift devices is sustained.In addition,a considerable noise reduction is observed in the downward direction.With detailed analysis of the time-averaged and instantaneous flow fields,two mechanisms are identified as the reason accounting for the noise suppression：upstream mass injection significantly reduces the scale and strength of the vortices stemming from the cusp;the shear layer is lifted up,which relieves the shear layer impingement on the slat lower surface.